2024
DOI: 10.1136/pn-2023-003918
|View full text |Cite
|
Sign up to set email alerts
|

Management of carotid atherosclerosis in stroke

Nicholas Richard Evans,
Shiv Bhakta,
Mohammed M Chowdhury
et al.

Abstract: Internal carotid artery atherosclerosis is a major risk factor for stroke, accounting for 15–20% of ischaemic strokes. Revascularisation procedures—either carotid endarterectomy or carotid artery stenting—can reduce the risk of stroke for those with significant (>50%) luminal stenosis but particularly for those with more severe (70–99%) stenosis. However, advances in medical pharmacotherapy have implications for the relative benefit from surgery for symptomatic carotid atherosclerosis, as well as our approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Some authors propose it as a regulated process based on histological resemblance to trabecular bone. Histological studies demonstrated mild calcifications are associated with soft plaque and medium-to-severe calcifications are associated with hard plaques [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors propose it as a regulated process based on histological resemblance to trabecular bone. Histological studies demonstrated mild calcifications are associated with soft plaque and medium-to-severe calcifications are associated with hard plaques [ 17 ].…”
Section: Discussionmentioning
confidence: 99%